1995
DOI: 10.1051/animres:199505129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of saponins from Sapindus Rarakfruit on rumen microbes and host animal growth

Abstract: The aim of this paper focuses on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 0 publications
4
24
1
1
Order By: Relevance
“…A similar observation was made by Thalib et al (1996) who reported that total cellulolytic bacteria increased when sheep were fed with a methanol extract of S. rarak. However, a dramatic decrease in the RNA concentration of Ruminococci in short-term feeding of S. rarak extract and disappearance of this effect upon long term feeding indicated that there may be an adaptation of Ruminococcus sp.…”
Section: Plants Containing Saponinssupporting
confidence: 83%
See 1 more Smart Citation
“…A similar observation was made by Thalib et al (1996) who reported that total cellulolytic bacteria increased when sheep were fed with a methanol extract of S. rarak. However, a dramatic decrease in the RNA concentration of Ruminococci in short-term feeding of S. rarak extract and disappearance of this effect upon long term feeding indicated that there may be an adaptation of Ruminococcus sp.…”
Section: Plants Containing Saponinssupporting
confidence: 83%
“…Based on these results, Newbold et al (1997) suggested feeding saponins intermittently to prevent a quick increase in protozoal counts in the rumen. Thalib et al (1996) showed that feeding saponin extract every 3rd day kept the protozoal counts low even after 3 weeks. On the other hand, S. rarak saponins did not lose their defaunating activity until 27 days when fed to sheep (Wina et al, 2005a).…”
Section: Plants Containing Saponinsmentioning
confidence: 99%
“…Saponins are glycosides which apparently interact with the cholesterol present in eukaryotic membranes but not in prokaryotic cells [17]. A decrease in protozoal numbers was reported in the rumen of sheep infused with pure saponin [76] or fed saponin-containing plants [29,102,106,109,135,136]. However, even if a practical on-farm method to remove protozoa from the rumen can be found, the effects of defaunation on methane emissions can not be considered in isolation.…”
Section: Defaunationmentioning
confidence: 99%
“…A total of 38 articles consisting of 137 data points (represented different dietary treatments) were integrated into the database (Mathius et al, 1996;1997;Thalib et al, 1996;Lubis et al, 1998;2002;Mahyuddin, 2001;Duldjaman, 2004;Tarmidi, 2004;Adawiyah et al, 2006;Puastuti et al, 2006;Uhi, 2006;Supriati & Haryanto, 2007;Wiryawan et al, 2007;Sudarman et al, 2008;Supriyati, 2008;Tanuwiria & Ayuningsih, 2008;Thalib & Widiawati, 2008;Zain, 2009;Hartutik et al, 2010;Hernaman et al, 2011;Widiyanto et al, 2011;Rimbawanto et al, 2012;Ketaren et al, 2013;Sitanggang et al, 2013;Braymana et al, 2014;Ekawati et al, 2014;Khotijah et al, 2014;Nababan et al, 2014;Ndaru et al, 2014;Wulandari et al, 2014;Aqbari et al, 2015;Simanjuntak et al, 2015;Tiven et al, 2015;Wati et al, 2015). Different breeds (Priangan, fat-tailed and local) and sexes (male and female) were specified in the database.…”
Section: Database Developmentmentioning
confidence: 99%